The Impact of Teacher’s Reinforcement Toward Students’ English Learning Motivation - Ananda Salsabilah Ramadhani; Maemuna Muhayyang; Munir Munir (Journal of Excellence in English Language Education, 2023)
This study aims to find out (1) the kinds of reinforcement that the teacher uses toward students’ English learning motivation and (2) how the teacher’s reinforcement impact toward students’ English learning motivation. The subject of this study consists of six students of XI IPA 2 MAN 1 Kolaka. They were recruited using cluster random sampling. The results of this study indicate that (1) the teacher and students interact well in the teaching and learning process with the existence of verbal and non-verbal reinforcement; (2) the teacher reinforcement in the form of giving additional points, responding with facial mimics, motivation and sentences of praises has a positive impact toward students’ English learning motivation. In conclusion, the kinds of reinforcement teachers use toward students’ English learning motivation are verbal reinforcement and non-verbal reinforcement and there are four ways teacher’s reinforcement impacts students’ English learning motivation, those are giving additional points, responding with facial mimics, giving sentences of praise and giving motivation.